2021
DOI: 10.1200/jco.21.00079
|View full text |Cite
|
Sign up to set email alerts
|

Pembrolizumab Plus Ipilimumab Following Anti-PD-1/L1 Failure in Melanoma

Abstract: PURPOSE Combination of antiprogrammed cell death protein-1 (PD-1) plus anti–cytotoxic T-cell lymphocyte-4 (anti-CTLA-4) immunotherapy shows greater response rates (RRs) than anti-PD-1 antibody alone in melanoma, but RR after initial anti-PD-1 and programmed death ligand-1 (PD-L1) antibody progression awaits robust investigation. Anti-CTLA-4 antibody alone after anti-PD-1/L1 antibody progression has a historical RR of 13%. We report the results of the first prospective clinical trial evaluating ipilimumab 1 mg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
104
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(113 citation statements)
references
References 27 publications
8
104
0
1
Order By: Relevance
“…42 In a small prospective study of pembrolizumab plus low-dose ipilimumab (1 mg/kg), the ORR was 29% in all enrolled patients. 43 In our study, the DCRs at week 18 were comparable in patients treated with ipilimumab and ipilimumab plus nivolumab. Notably, the elapsed time interval between the last dose of anti-PD-1 monotherapy and the study drug was short in both arms: 6 weeks (range 3–55 weeks) in patients treated with ipilimumab arm and 4.3 (range 2–36 weeks) in patients treated with ipilimumab plus nivolumab.…”
Section: Discussionsupporting
confidence: 53%
“…42 In a small prospective study of pembrolizumab plus low-dose ipilimumab (1 mg/kg), the ORR was 29% in all enrolled patients. 43 In our study, the DCRs at week 18 were comparable in patients treated with ipilimumab and ipilimumab plus nivolumab. Notably, the elapsed time interval between the last dose of anti-PD-1 monotherapy and the study drug was short in both arms: 6 weeks (range 3–55 weeks) in patients treated with ipilimumab arm and 4.3 (range 2–36 weeks) in patients treated with ipilimumab plus nivolumab.…”
Section: Discussionsupporting
confidence: 53%
“… 551 Of note, improved antitumor response and tolerable safety are seen in anti-PD-1/PD-L1-refractory melanoma patients with pembrolizumab plus low-dose ipilimumab. 552 The treatment of other types of melanoma excluding cutaneous melanoma is of great challenge for their relatively insensitive response to existing therapies. The combination of nivolumab and ipilimumab has been subsequently evaluated in non-cutaneous melanoma including acral, mucosal, and uveal melanoma, and the combination regimen shows sustained and improved response compared with either single agent, although with elevated toxicity but manageable safety profile.…”
Section: Present Advances In Therapies Targeting Tumor Immunology and Ongoing Clinical Trialsmentioning
confidence: 99%
“…This combination approach has become the most intensively studied as well as the most widely used immune combination regimen (103). Daniel et al (104) evaluated the efficacy of Pembrolizumab plus Ipilimumab in melanoma patients after failure of anti-PD-1/PD-L1 therapy and showed that 29% of patients achieved a confirmed response (including 21.4% partial responses and 7.2% complete responses). This demonstrates the significant antitumor activity of the combination.…”
Section: Ctla-4 Inhibitorsmentioning
confidence: 99%